IMPROVING WRITING SKILL OF THE TENTH-GRADE STUDENTS OF SMKN 2 DENPASAR IN ACADEMIC YEAR 2020/2021 THROUGH ESA COMBINED WITH PICTURE - Made Ayu Sarika Pratiwi; I Komang Budiarta; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2021)
Amongst four English skills, writing becomes pivotal, and students must be capable in thisskill. Writing is a communication form where the writer delivers and arrange ideas into areadable form for a specific purpose. The present research was mainly based on thepreliminary observation towards 32 subjects in the X BDPM 1 class at SMKN 2 Denpasar inacademic year 2020/2021. The results showed that most of the subjects’ writing skill was stilllow. Besides, the present research was aimed at investigating whether or not the writing skillof the tenth-grade students of SMKN 2 Denpasar can be improved through ESA combined withpicture. To achieve the objective, the researcher conducted classroom action research whichwas done in two cycles. Furthermore, the required data were obtained by administering theresearch instruments: tests and a questionnaire. The collected data were then analyzed bycomparing the pre-test and post-tests, which showed significant improvements in the subjects’mean scores from the pre-test to post-tests. Furthermore, the questionnaire results showed thatthe subjects’ positive responses toward the implementation of ESA combined with picture. Itcould be concluded that writing skill of the tenth-grade students of SMKN 2 Denpasar inacademic year 2020/2021 can be improved through ESA combined with picture.